THE EFFECTIVENESS OF AUDIO AS AN ALTERNATIVE MEDIA IN IMPROVING STUDENTS' LISTENING COMPREHENSION ACHIEVEMENT: Listening Comprehension - Dedek Suprihatin, Dedek; Angraini, Nike; Iman, Jaya Nur (Journal of English Language and Literature Teaching, 2023)
In order to develop the listening skill, there are many kinds of media that can be used, including CD, tape record, audio, video, etc. However, the researcher chose audio as a media in teaching and learning. Therefore, the objectives of this study were to find out if there was a significant improvement on students’ listening comprehension achievement after being taught by using audio. The other one was that if there was a significant mean difference between the students who were taught by using audio and those who were not. The research method was a quantitative. Furthermore, the researcher employed an experimental study. As a design, the researcher employed a quasi-experimental study. The population of this research were all of the second year of SMP Negeri 38 Palembang students. Therefore, the researcher took VIII.3 class (experimental) and VIII.7 class (control) for being the sample. The researcher employed a fill in the blank test, true false, multiple choices, matching the answer, order, and matching the phrases as the primary instrument to collect data. The researcher used the Paired and Independent Sample T-Test formula to calculate the data. With regard to the effect of using audio as an alternative method in improving students’ listening comprehension achievement, the result of Paired Sample T-test reveals that using audio as an alternative method has a positive effect. According to the outcomes of the independent sample t-test, there was a significant difference between the post-test scores of control and experimental class. It can be concluded that audio gave positive effect on the students’ listening comprehension achievement of SMP Negeri 38 Palembang.